Pseudo broad ligament fibroid mimicking ovarian malignancy: a case report - Naghma, Shahida; Meena, Mamta Kumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Fibroids are smooth muscle benign tumors. They arise most commonly from the uterus but may also rise from extra uterine sites like broad ligament. Uterine fibroids are the most common myomas, while uterine cervix and intraligamentary fibroids are statistically less frequent. This case report of Pseudo broad ligament fibroid with extensive cystic degeneration is presented for its rarity and diagnostic challenges as they mimic pelvic adenexal tumors. Following is the case report of a 40 year old, P4L4, postmenopausal female admitted in the department due to a diagnosed solid lesion in the left adnexa. Patient was asymptomatic 3 months back when she noted gradual swelling and distention over the abdomen. On abdomen examination, a generalized mass was palpable with minimal ascites. On ultrasonography, a large heterogenous mass measuring 200X215 mm seen in pelvic region, arising from left adnexa and extending towards abdomen. During laparotomy, left sided fibroid was removed and sent for frozen section analysis. Histopathological reports revealed spindle cells arranged in fascicles and interlacing bundle with focal areas of myxoid degeneration. Huge pseudo-broad ligament leiomyoma with cystic degeneration may present diagnostic difficulties in differentiating ovarian malignancies even on ultrasound and MRI. This differential diagnosis must be considered prior to surgical management.